Factors Impacting Online Ratings for Otolaryngologists. (August 2018) - Calixto, Nathaniel E.; Chiao, Whitney; Durr, Megan L.; Jiang, Nancy
Objective: To identify factors associated with online patient ratings and comments for a nationwide sample of otolaryngologists. Methods: Ratings, demographic information, and written comments were obtained for a random sample of otolaryngologists fromHealthGrades.com andVitals.com . Online Presence Score (OPS) was based on 10 criteria, including professional website and social media profiles. Regression analyses identified factors associated with increased rating. We evaluated for correlations between OPS and other attributes with star rating and used chi-square tests to evaluate content differences between positive and negative comments. Results: On linear regression, increased OPS was associated with higher ratings on HealthGrades and Vitals; higher ratings were also associated with younger age on Vitals and less experience on HealthGrades. However, detailed correlation studies showed weak correlation between OPS and rating; age and graduation year also showed low correlation with ratings. Negative comments more likely focused on surgeon-independent factors or poor bedside manner. Conclusion: Though younger otolaryngologists with greater online presence tend to have higher ratings, weak correlations suggest that age and online presence have only a small impact on the content found on ratings websites. While most written comments are positive, deficiencies in bedside manner or other physician-independent factors tend to elicit negative comments.